2021
DOI: 10.21203/rs.3.rs-243054/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic markers for the biological responses of Triclosan stressed hatchlings of Labeo rohita

Abstract: Triclosan (TCS) used commonly in pharmaceuticals and personal care products has become the most common pollutant in water. Three days old hatchlings of an indegenous fish, Labeo rohita were given 96h exposure to an environmentally relevant (0.06mg/L) and two moderately lethal concentrations (0.067 and 0.097 mg/L) of TCS and kept for 10 days of recovery for recording transcriptomic alterations in antioxidant/detoxification (SOD, GST, CAT, GPx, GR, CYP1a and CYP3a), metabolic (LDH, ALT and AST) and neurologica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Significant decrease in the intensity of these peaks after recovery may be linked with either oxidation of proteins under the influence of accumulated ROS or their metabolism to fulfil higher energy demand in the stressed hatchlings. In our previous studies (Sharma et al, 2021a;2021b), we observed a significant decline in protein content in the TCS exposed hatchlings and this directly supports the present observations. Similarly, altered intensity of amide A, amide I and amide II has also been reported in the TCS exposed embryos/larvae of four food fishes (Dar et al, 2022) and in liver, muscle, brain and kidney of arsenic exposed fingerlings of L. rohita (Palaniappan and Vijayasundaram, 2008a;Palaniappan and Vijayasundaram, 2008b;Palaniappan and Vijayasundaram, 2009a;Palaniappan and Vijayasundaram, 2009b).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Significant decrease in the intensity of these peaks after recovery may be linked with either oxidation of proteins under the influence of accumulated ROS or their metabolism to fulfil higher energy demand in the stressed hatchlings. In our previous studies (Sharma et al, 2021a;2021b), we observed a significant decline in protein content in the TCS exposed hatchlings and this directly supports the present observations. Similarly, altered intensity of amide A, amide I and amide II has also been reported in the TCS exposed embryos/larvae of four food fishes (Dar et al, 2022) and in liver, muscle, brain and kidney of arsenic exposed fingerlings of L. rohita (Palaniappan and Vijayasundaram, 2008a;Palaniappan and Vijayasundaram, 2008b;Palaniappan and Vijayasundaram, 2009a;Palaniappan and Vijayasundaram, 2009b).…”
Section: Discussionsupporting
confidence: 92%
“…The band at 1082-1083 cm −1 specifies asymmetric stretching of phosphodiester group of nucleic acids. Significant decline in the area of this band indicates low contents of nucleic acids (DNA and RNA) in the hatchlings and is also indicative of the genotoxic potential of TCS (Hemalatha et al, 2019;Gyimah et al, 2020;Sharma et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations